INTENSITAS SERANGAN PENGGEREK BATANG PADI PUTIH (Scirpophaga innotata) WALKER (LEPIDOPTERA : PYRALIDAE) DAN MUSUH ALAMI PADA DUA TEMPAT DENGAN KETINGGIAN YANG BERBEDA - Afandi, Afandi; Yunus, Mohammad; Hasriyanty, Hasriyanty (AGROTEKBIS, 2018)
Rice is the most important food crop in Indonesia, as more than half of populations inIndonesia depends their life on rice produced from rice plants. This research aims to determine the intensity of white rice stem boreron thetwo different places, namely the plateau in the Sejahtra village, Palolo Subdistrict at an altitude of 592 meters above the sea (masl), and the lowland area in Lolu village, Sigi Biromaru Subdistrict, Sigi Regency at an altitude of 171 (masl). Whereas its usefulness is to compare the level of attacks that occur in the field by white rice stem borer. This research was conducted in the rice cultivation area at two different places altitudes and the implementation time from April to July 2016. The research was conducted with the survey method, observation and execution of research. The variable of observation namely, 1) The intensity of S.innotata pests. 2) The number of pest eggs S.innotata group and 3)The types and the numbers of parasitoids. Therw is the difference in the intensity of S.innotata attacks in two areas in different heights. Attacks on Oloboju are higher (35%) while attacks on Sejahtera are lower (10%) and there are three species of parasitoid in the S.innotata'segg, they are parasitoid of Telenomus, sp., Tetrastichus, sp.,and Trichogramma, sp.Telenomus, sp. More dominant to of fendin Oloboju while, sp. More dominant to of fendin Sejahtera.